2014
DOI: 10.5505/abantmedj.2014.40326
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in the Gastric Cancer: 504 Cases

Abstract: Objective: Gastric cancer is the second most common cause of cancer-related deaths. It is mostly seen between the ages of 50-70 years. In our study, we aimed to present our 11 years of experience about surgical treatment of gastric cancer. Method: In our medical faculty hospital between January 2000 and December 2010, a total of 504 patients, who operated with the diagnosis of gastric cancer, were analyzed retrospectively. Morbidity and mortality rate were evaluated according to type of operations and risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…In recent years, frequencies of gastric cancers that are located at antrum and corpus has been reported to decrease, and gastric cancers that are located at cardia has been reported to increase [17]. Coşkun et al reported that 45.5% of esophageal tumors were located at distal esophagus and 40.7% of gastric tumors were located at the corpus [10].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, frequencies of gastric cancers that are located at antrum and corpus has been reported to decrease, and gastric cancers that are located at cardia has been reported to increase [17]. Coşkun et al reported that 45.5% of esophageal tumors were located at distal esophagus and 40.7% of gastric tumors were located at the corpus [10].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of gastric cancer in our country varies between 0.5-4% (17). In a study involving 504 gastric cancers in Erzurum Region, 36.1% of gastric cancer patients were female and 63.9% male, and the mean age of the patients was 62.4 years (22).…”
Section: Discussionmentioning
confidence: 99%